2020
DOI: 10.1016/j.ajem.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of SOFA and qSOFA for in-hospital mortality in severe novel coronavirus disease

Abstract: Objectives The assessment of illness severity at admission can contribute to decreased mortality in patients with the coronavirus disease (COVID-19). This study was conducted to evaluate the effectiveness of the Sequential Organ Failure Assessment (SOFA) and Quick Sequential Organ Failure Assessment (qSOFA) scoring systems at admission for the prediction of mortality risk in COVID-19 patients. Methods We included 140 critically ill COVID-19 patients. Data on demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 26 publications
1
142
1
2
Order By: Relevance
“…Unit increase in SOFA score was associated with high odds of mortality in our data. Since SOFA tends to reflect the effect on multiple organ systems, it has proved to be a better predictor of mortality in COVID-19 [24]. Some desperate therapies used globally including Hydroxychloroquine and azithromycin (alone or in combination), therapeutic anticoagulation, antibiotics, two doses of Tocilizumab and IVIG showed increased odds of mortality which when adjusted for other factors became insignificant in the final model.…”
Section: Discussionmentioning
confidence: 99%
“…Unit increase in SOFA score was associated with high odds of mortality in our data. Since SOFA tends to reflect the effect on multiple organ systems, it has proved to be a better predictor of mortality in COVID-19 [24]. Some desperate therapies used globally including Hydroxychloroquine and azithromycin (alone or in combination), therapeutic anticoagulation, antibiotics, two doses of Tocilizumab and IVIG showed increased odds of mortality which when adjusted for other factors became insignificant in the final model.…”
Section: Discussionmentioning
confidence: 99%
“…Host factors predictive of severe clinical course and adverse outcome in patients with Coronavirus disease 2019 (COVID-19) include older age, male gender, and preexisting chronic comorbidities [1][2][3][4][5][6]. Several risk scores containing clinical characteristics, laboratory assessments, and biomarkers have been proposed for improved patient management and resource allocation [5,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the rate of mortality may increase two-to tenfold among patients admitted to the intensive care unit (ICU) with pre-existing morbidities such as cardiovascular disease and diabetes [1,3]. Li et al [3] reported that the mortality rate of patients with hypertension, cerebrovascular diseases, and diabetes was two-, three-, and twofold higher in patients admitted to the ICU, respectively. The main risk factors of mortality are older age, shortness of breath or dyspnea, low level of hemoglobin, and underlying comorbidities.…”
Section: Introductionmentioning
confidence: 99%